2018
DOI: 10.1371/journal.pone.0200180
|View full text |Cite
|
Sign up to set email alerts
|

Priming of leaf litter decomposition by algae seems of minor importance in natural streams during autumn

Abstract: Allochthonous detritus of terrestrial origin is one of the main energy sources in forested headwater streams, but its poor nutritional quality makes it difficult to use by heterotrophs. It has been suggested that algae growing on this detritus can enhance its nutritional quality and promote decomposition. So far, most evidence of this "priming effect” is derived from laboratory or mesocosm experiments, and its importance under natural conditions is unclear. We measured accrual of algae, phosphorus uptake capac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 59 publications
3
12
0
Order By: Relevance
“…Moreover, from a subset of studies we found that algae can shift pools of microbial and detrital C, N, and P within decomposing litter-periphyton. As expected from our third hypothesis, we found weak algal effects on N-and P-specific mass loss from litter-periphyton during decomposition, possibly because algal immobilization counterbalances algal effects on heterotrophic mineralization of litter N and P (Halvorson et al, 2016;Elosegi et al, 2018), or perhaps due to the wide variation in priming intensity across datasets. The small sample size and large variation revealed by our meta-analysis suggest that additional studies are needed to further assess the overall priming effect, its dependence on environmental factors such as N:P availability, and its implications for coupled elemental transformations in aquatic ecosystems.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Moreover, from a subset of studies we found that algae can shift pools of microbial and detrital C, N, and P within decomposing litter-periphyton. As expected from our third hypothesis, we found weak algal effects on N-and P-specific mass loss from litter-periphyton during decomposition, possibly because algal immobilization counterbalances algal effects on heterotrophic mineralization of litter N and P (Halvorson et al, 2016;Elosegi et al, 2018), or perhaps due to the wide variation in priming intensity across datasets. The small sample size and large variation revealed by our meta-analysis suggest that additional studies are needed to further assess the overall priming effect, its dependence on environmental factors such as N:P availability, and its implications for coupled elemental transformations in aquatic ecosystems.…”
Section: Discussionsupporting
confidence: 83%
“…The ecological stoichiometry of priming effects remains comparatively understudied in aquatic systems, where priming can be significant (e.g., Danger et al, 2013;Bianchi et al, 2015), yet the general direction and magnitude of priming effects are strongly debated due to incongruent evidence (Bengtsson et al, 2018;Elosegi et al, 2018). Some studies suggest that increased dissolved N and P concentrations may shift priming from positive to negative, by stimulating algal growth and exudation of labile C and enabling preferential use of labile C by microbial heterotrophs in lieu of recalcitrant detrital C (Guenet et al, 2010;Guillemette et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of our study streams, k f contributed more to k c than λ F for broadleaf litter, which has been previously observed (Elosegi, Nicolás, & Richardson, ; Yeung et al., ). Thus, litter–microbe interactions appeared to play a more essential role than litter–shredder interactions in mediating early‐stage breakdown (i.e.…”
Section: Discussionsupporting
confidence: 81%
“…Less information is available on the roles of yeasts, zoosporic fungi, oomycetes, and protists, but they were found to be associated with decomposing leaf litter and can affect litter decomposition directly or indirectly via trophic interactions [32][33][34][35][36]. The role of algae on litter decomposition is also uncertain with some studies suggesting that they can stimulate litter decomposition via microbial priming (i.e., the stimulation of microbial decomposers' activity by the addition of labile carbon) [37], while other studies found inhibition or no effect [38,39]. Microbial activity leads to litter mass loss through the release of fine particles and dissolved litter mass, incorporation of litter carbon into microbial biomass (including reproductive structures that are released), and carbon mineralization [40][41][42].…”
Section: Phases and Key Playersmentioning
confidence: 99%